PENERAPAN MODEL PEMBALAJARAN KOOPERATIF TIPE QUICK ON THE DRAW UNTUK MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA PADA MATERI PECAHAN SISWA KELAS III SDN 001 PAGARAN TAPAH DARUSSALAM KABUPATEN ROKAN HULU - Maidar Maidar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
This study aims to determine whether there is an increased motivation to learn mathematics of third grade students of SDN 001 Pagaran Tapah Darussalam Rokan Hulu after application of cooperative learning model of quick on the draw. The problems of the research is "What type of cooperative learning model of application quick on the draw can Increase the motivation to learn mathematics 001 third grade students of SDN Pagaran Tapah Darussalam Rokan Hulu?" This research is a classroom action research conducted in SDN 001 Pagarah Tapah Darussalam. The subjects were students of class III is 31 students. Collecting the data in this study using sheets of observations made every meeting. Based on the results of this study concluded that using cooperative learning model of the type of quick on the draw can Increase the motivation to learn mathematics 001 third grade students of SDN Pagaran Tapah Darussalam Rokan Hulu.Keywords: cooperative quick on the draw, the motivation to learn math